2020
DOI: 10.1002/adfm.202007129
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Solid‐State Direct Ethanol Fuel Cell Catalyzed by Nanoporous High‐Entropy Al‐Pd‐Ni‐Cu‐Mo Anode and Spinel (AlMnCo)3O4 Cathode

Abstract: As in many other electrochemical energy‐converting systems, the flexible direct ethanol fuel cells rely heavily on high‐performance catalysts with low noble metal contents and high tolerance to poisoning. In this work, a generic dealloying procedure to synthesize nanoporous multicomponent anodic and cathodic catalysts for the high‐performance ethanol fuel cells is reported. On the anode side, the nanoporous AlPdNiCuMo high‐entropy alloy exhibits an electrochemically active surface area of 88.53 m2 g−1Pd and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 72 publications
0
33
0
Order By: Relevance
“…Computational investigations suggested that the increased covalency of the Ir─O bond in the surface mixed oxide sites is the main contribution to the enhanced OER activity. Analogously, Qiu et al ( 91 ) prepared AlNiCoFeX (X = Mo, Nb, and Cr) nanostructures with oxide surface layers as alkaline OER catalysts, which were further integrated into the flexible direct ethanol fuel cells ( 92 ).…”
Section: Heas For Catalysismentioning
confidence: 99%
“…Computational investigations suggested that the increased covalency of the Ir─O bond in the surface mixed oxide sites is the main contribution to the enhanced OER activity. Analogously, Qiu et al ( 91 ) prepared AlNiCoFeX (X = Mo, Nb, and Cr) nanostructures with oxide surface layers as alkaline OER catalysts, which were further integrated into the flexible direct ethanol fuel cells ( 92 ).…”
Section: Heas For Catalysismentioning
confidence: 99%
“…viii) Dealloying method. [32,37,41,43,54] The method is suitable for high yield, more suitable for industrial application, and easy to prepare porous high entropy alloy with pore structure. However, the high temperature and inert atmosphere conditions in the early stage of the casting process lead to high cost.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of nanotechnology, HEAs have also made progress in the electrocatalysis field. [21][22][23][24][25][26][27] It can be effectively used for hydrogen evolution reaction (HER), [28][29][30][31][32][33][34][35][36][37] oxygen evolution reaction (OER), [18,29,30,[38][39][40][41][42] oxygen reduction reaction (ORR), [32,41,[43][44][45][46][47] alcohol oxidation reaction (MOR/EOR), [34,43,[48][49][50][51][52][53][54] carbon dioxide reduction reaction (CO 2 RR), [55,56] and nitrogen reduction reaction (NRR). [57] In catalysis, the excellent performance of the material is not just a simple superposition of the performance of each metal ion, but comes from the synergy between the metal ions.…”
Section: Multi-sites Electrocatalysis In High-entropy Alloysmentioning
confidence: 99%
“…[289] Particularly, the high-entropy alloys have been intensively developed in ORR electrocatalysis. [295][296][297] Hu's group developed a high-throughput method to synthesize an extensive series of HEAs to rapidly screen for highly-efficient electrocatalysts using a scanning droplet cell (Figure 10d). [135] The samples with varied ORR activities were displayed in a neural network diagram, where the size of the circles represented the magnitude of the specific current at 0.45 V (Figure 10e).…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%